Reimagining Speech Therapy for Developmental Language Disorder through Music and Digital Practice - Sandryna Rachella Sander; Fuji Astuti; Ardipal; Indrayuda (Program Studi Pendidikan Musik FBS UNP, 2026)
Purpose: This study aims to examine the representation of speech therapy practices for children with Developmental Language Disorder (DLD) through the use of the nursery rhyme “Bingo”, as manifested in professional digital interactions. Methods: The study employs a descriptive qualitative approach by examining narrative, comments, and professional reflections shared by speech therapist, support teacher, and special education practitioner on professional digital platforms. This approach enables an in depth understanding of the experiences, strategies, and practical meanings that envolve within the digital ecosystem. Results and Discussion: Findings reveal that the nursery rhyme “Bingo” is represented as an applicable, flexible, and easily adaptable therapeutic medium in field practice. The song’s characteristics as repetitive lyrics, a simple rhythmic structure, and the integration of body movements are perceived as effective in stimulating both receptive and expressive language abilities in children with DLD. Professional digital interactions function not only as spaces for sharing experiences but also as sources of collective practical knowledge that complement theoretical perspectives in speech therapy. Conclusion: The use of the nursery rhyme “Bingo” in speech therapy for children with DLD can be understood as an experience-based professional practice that develops collaboratively through digital platforms. Professional digital interactions play a crucial role in strengthening the dissemination of effective practices and supporting the development of contextual, adaptive, and sustainable speech therapy approaches.